Pembatalan Putusan Arbitrase di Indonesia Menurut Undang-Undang Nomor 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa - Soni Septiyanda; Abdurrahim Abdurrahim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is conducted to comprehensively analyze the legal provisions related to the annulment of arbitral awards in Indonesia based on Law Number 30 Year 1999, identify obstacles in practice, and provide recommendations for strengthening the arbitration system as a reliable alternative dispute resolution. This research is a normative legal study that uses an approach through literature review and statutory analysis. The data used includes primary data in the form of legal literature related to the law, as well as secondary data which includes primary, secondary, and tertiary legal materials. Data collection is done through document study method and literature review. The data analysis was conducted using a qualitative descriptive approach to interpret the legal materials collected. The results of this study indicate that the district court has an important role in enforcing the financial principle of arbitral awards, there are limited opportunities for annulment and efforts to balance the protection of justice and legal certainty in resolving arbitration disputes. Meanwhile, the implications are very significant for the parties as well as the effectiveness and reputation of the arbitration system itself.